Getting our hopes up: How actors perceive network effectiveness and why it matters. (May 2023) - Peeters, Robin; Westra, Daan; van Raak, Arno J.A.; Ruwaard, Dirk
Abstract: Health care's grand challenges, such as continuously increasing costs, challenge the sustainability of health systems. Purpose-oriented networks are considered a favorable mode of organization to address these grand challenges. Therefore, it is crucial that they are effective. While network effectiveness is a heavily theorized, multi-dimensional concept that is often measured as a perception of actors, little is known about how network actors perceive effectiveness in practice and how this influences their behavior. In this study, we explored how network actors perceive network effectiveness using 32 interviews with representatives from network member organizations and regulatory agencies actor, 28 h of network meeting observations, and 1.272 pages of documents such as meeting minutes and media outlets. Our results show that actors primarily see hard outcomes (e.g. changes in cost or quality of care) as effectiveness but given the temporal nature of these goals and difficulties quantifying them, they resort to the collaborative process as a proxy to assess effectiveness. Actors engage in networks to solve grand challenges. However, conforming to expectations and environmental pressures also play a substantial role for actors to (continue to) participate in networks. In the absence of hard outcomes, actors legitimize their continued participation in networks using the collaborative process of networks. Actors therefore take purpose-oriented networks for granted as a legitimate way of organizing. Besides attempting to solve grand challenges, networks thus also seem to be adopted because of powerful institutional rules that function as rationalized myths, to gain legitimacy. Future research should be aware of and further unravel the institutional pressures in networks. Highlights: Policy pushes call for collaboration in networks to keep health systems sustainable. Measuring hard outcomes of networks is deemed necessary yet difficult in practice. The collaborative process is used as proxy to legitimize ineffective networks. Normative and coercive pressures force stakeholders to keep collaborating. Purpose-oriented networks are established, partly, as institutionalized myths.